OPTIMALISASI PENDISTRIBUSIAN DANA ZAKAT UNTUK MENINGKATKAN KESEJAHTERAAN MUSTAHIK (Studi Kasus Baznas Kota Malang) - Dian Novitasari; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2022)
Amil zakat agency is a zakat management institution formed by the government, consisting of government and community elements with the task of collecting, distributing, and utilizing zakat. As this is done by the National Amil Zakat Agency (BAZNAS) Malang. as a zakat management institution BAZNAS Malang City must be able to provide tangible evidence to the community in the distribution of productive zakat that is right on target and successfully fights poverty. This type of research is a qualitative research and uses a descriptive approach conducted at BAZNAS Malang City using a descriptive approach. Sources of data in this study consisted of primary and secondary data sources obtained through interviews and documentation. This study resulted in the following conclusions. First, optimizing the distribution of zakat in improving the welfare of mustahik in BAZNAS Malang City greatly supports mustahik who need capital, tools, for business development. infaq and sadaqah. So that the public knows that the magnitude of the potential of ZIS can help government programs in alleviating poverty. Second, this program has an influence on the welfare of mustahik by increasing business results, reducing basic needs, increasing family income and increasing knowledge, skills, as well as independence.